Emil Bratz (1868–1934): the life and work of an early German epileptologist Emil Bratz (1868–1934): Leben und Werk eines frühen deutschen Epileptologen - Kasper, Burkhard S.; Hebold, M.; Stockmann, J. P. (Clinical Epileptology, 2025)
Emil Bratz (1868–1934) was a German neuropsychiatrist who worked in Berlin institutions until 1933. From 1894 to 1910 he was affiliated with Berlin-Wuhlgarten, one of the first hospitals and colonies dedicated exclusively to epilepsy patients in Europe. From the beginning of his career, he actively researched the topic of epilepsy including pathoanatomical microscopic studies of Ammon’s horn starting before 1900. At the beginning of the 20th century, he wrote extensively on the topic of epilepsy. Furthermore, he represented Germany in the founding years of the International League Against Epilepsy (ILAE) and belonged to the group that established the journal Epilepsia. Here we commemorate Emil Bratz, an early but largely forgotten epileptologist, by presenting the first comprehensive synopsis of Bratz’s life and work including new information from first-hand materials, illustrating his professional career and research activities as an epileptologist, providing a full list of his publications on epilepsy, and describing his role in the founding years of ILAE and Epilepsia. As we show, Emil Bratz deserves to be remembered for his important contributions to the rise of epileptology at the turn of the 20th century.
CRIS-Team Scopus Importer:2025-03-28
Keywords: Ammon’s horn sclerosis; Epilepsy; Hebold; Pathoanatomy; Wuhlgarten